جهود الإمام الحسين بن علي بن طلحة الرجراجي الشوشاوي (ت 899هـ) وآراؤه في خدمة كتاب الله تعالى - شبرو،, ليلى (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2023)
ملخص الدراسة بالعربية: الحمد لله رب العالمين، والصلاة والسلام على أشرف الأنبياء والمرسلين، أما بعد: فهذا البحث الذي وسمته بـ"جهود الإمام الرجراجي الشوشاوي(ت 899هـ) وآراؤه في خدمة كتاب الله تعالى"، هو بمثابة عرض لجهود الإمام الرجراجي الشوشاوي رحمه الله وآرائه في خدمة كتاب الله تعالى، وذلك عبر ثلاثة فصول: فصل تمهيدي تناولت فيه حياة الإمام الشخصية والعلمية، مع إلقاء نظرة يسيرة عن العصر الذي عاش فيه. أما الفصل الأول فقد تطرقت فيه لجهود الإمام في خدمة كتاب الله تعالى من خلال مؤلفاته في: القراءات والتجويد، الرسم القرآني، الضبط القرآني، وعلوم القرآن المختلفة. أما الفصل الثاني فتناولت فيه آراء الإمام في: القراءات والتجويد، الرسم القرآني، الضبط القرآني، وعلوم القرآن. ليكلل البحث بخاتمة توصلت فيها إلى أهم النتائج ، ومنها: أنَّ الإمام الشوشاوي من العلماء الجهابذة الذين بذلوا حياتهم في خدمة كتاب الله تعالى من خلال مؤلفاته المتنوعة. أنَّ أغلب آراء الإمام وأقواله جاءت موافقة لما عليه أئمة الفنّ في مختلف فنون علوم القرآن. وفي الأخير أشرتُ إلى بعض التوصيات، ومن أهمها: الدعوة إلى الاعتناء أكثر بتراث الإمام الشوشاوي الذي لا يزال الكثير منه في حاجة إلى خدمة أهل العلم وطلابه، خاصة ما تعلّق منها بالقراءات والتجويد وعلم الرسم والضبط القرآني. The Abstract: praise be to Allah and peace and belessings be upon his messenger ،this research titled with :« The effort of Imam Al- RAJAJI Al Shushaoui 899 Hi »in service of the Quran،which considered to show of the effort of Imam and his views in service of studying Quran through three chapters. Introduction looked for the personal and professional life of the Imamin addition to a glimpse of his periodin the first chapter، I used to deal with the efforts of Imam in service of the holy book through his reading and Tajweed ، writing ، the correct form of Quranic verse and other sciences. The second Chapter l have taken the imam̕ s thoughts: readings and Tajweed ، Quranic drawing، the correct form of the Quranic verses. Also Quran sciences. The conclusion reached to the Important results such as Imam Al Shawshani ،(may God have meray on him) ، is one of the scholars who devoted their lives to the service of the noble Quran through many books. At the lengthI used to Impose some recommondation، the most Important is :preserving more the heritage of Imam Al Shawshani ،(may God have mercy on him) Huge number of students need his writings and thoughts.Most of the Imam’s opinions and sayings were in agreement with what most of the imams of art in the various arts of the sciences of the Qur’an،Sepacially readings andTajweed، Quranic drawings the correct form of Quranic verses.
أطروحة دكتوراه تخصص: علوم القرآن والتفسير في العوم الاسلامية
Keywords: علوم القرآن – جهود - أراء الامام الرجراجي الشوشاوي; Qur’anic sciences - efforts - opinions of Al-Imram Al-Rajraji Al-Shoshawi